Fatores associados ao manejo da sialorreia por cuidadores de crianças com microcefalia - Vasconcelos, Manuela Leitão de (2023)
Introduction: Microcephaly is a congenital malformation that interferes on brain development. Sialorrhea is a common condition in people with neurological disorders and can be understood as the involuntary loss of saliva. There are several impacts of sialorrhea on the lives of children and their caregivers, ranging from social conditions to health conditions. Objective: To identify factors related to the use of bibs in the management of sialorrhea by caregivers of children with microcephaly. Methodology: The research is characterized as primary, observational and cross-sectional. The sample consisted of 34 caregivers of children with microcephaly residing in the state of Paraíba. Volunteers were recruited using the “snowball” technique, indicated to access a rare population based on reference chains provided by the sample element's affinity social network. Caregivers of children with microcephaly born between 2015 and 2018 were included and malformation in the oral cavity was used as an exclusion criterion. The subjects in the sample answered two questionnaires, one about the birth and development of the child and the other about sialorrhea. Those who reported drooling and the use of a bib to manage it were contacted for 7 days to record the number of bibs used. The information was analyzed using the R software. For the descriptive analysis, measures of position and dispersion were used for quantitative variables and absolute frequency and percentage for qualitative variables. Machine learning models were then used to predict the number of bibs used per day. Results and discussion: Data show that caregivers are mostly mothers. Of the main caregivers, 91.18% are dedicated exclusively to child care. At the time of the interview, the average age of the children was 70.18 (±10.76) and all showed alterations in global motor development. With regard to food, there is a predominance of pasty consistency and use of inappropriate utensils for age. The complaint of sialorrhea was presented by 88.24% of the caregivers. Among the machine learning models considered, the one with the best performance was the Random Forest. The model pointed to 11 significant variables to explain the outcome. These variables address the oral motor development, the frequency and severity of sialorrhea and the impacts on the life of the child and their caregivers. Conclusion: The frequency of sialorrhea is the most significant variable; accompanied by aspects related to physical health and social impact of sialorrhea.